Strategic Management of Police Public Relations in Delivering Public Services: A Case Study of the Tanah Karo Regional Police - Zulham Zulham; Hasan Sazali; Hasnun Jauhari Ritonga (ETTISAL : Journal of Communication, 2025)
This research investigates the strategic communication management practices of the Tanah Karo District Police Public Relations (Polres Tanah Karo) unit in community service delivery. Employing a qualitative case study approach, it evaluates communication strategies, channels, and effectiveness in building positive community relations, guided by Harwood Childs' Public Relations Strategy theory encompassing publicity, persuasion, argumentation, and image-building alongside implicit elements of the Two-Way Symmetrical Model for mutual adaptation and Excellence Theory for stakeholder integration. Data collection involved in-depth interviews with police officers, community leaders, and residents, supplemented by document analysis and field observations. Findings reveal Polres Tanah Karo's multi-channel strategy, integrating digital platforms like Instagram, traditional media, and direct community engagement, which aligns with Childs' indicators for publicity and persuasion while addressing local cultural contexts. Challenges persist in message consistency, feedback mechanisms, and cultural sensitivity, highlighting needs for enhanced two-way symmetrical dialogue to counter inconsistencies and boost trust. This study advances insights into Indonesian police PR, demonstrating how adaptive frameworks improve community trust and service delivery in regional settings like North Sumatra.